Cultural studies: ¿un campo para todos los gustos? - Genaro Zalpa (Estudios sobre las Culturas Contemporáneas)
This paper intends to back the need for a theoretical definition of culture in Cultural Studies. The lack of theoretical definitions results in the shape of a field that is too nearly all tilings to all people, losing its original distinctive tlieoretical and metliodological strengtli. Tlieoredcal definitions of culture are needed to allow fruitful theoretical debate, and to clarify Cultural Studies 1 relationship witli political practices. Theoretical definitions of culture should address culture as meaning ;md should be placed witliin general theories of action.